ELemental abundances of Planets and brown dwarfs Imaged around Stars (ELPIS). I. Potential Metal Enrichment of the Exoplanet AF Lep b and a Novel Retrieval Approach for Cloudy Self-luminous Atmospheres - Zhoujian Zhang; Paul Mollière; Keith Hawkins; Catherine Manea; Jonathan J. Fortney; Caroline V. Morley; Andrew Skemer; Mark S. Marley; Brendan P. Bowler; Aarynn L. Carter; Kyle Franson; Zachary G. Maas; et al. (The Astronomical Journal, 2023)
AF Lep A+b is a remarkable planetary system hosting a gas-giant planet that has the lowest dynamical mass among directly imaged exoplanets. We present an in-depth analysis of the atmospheric composition of the star and planet to probe the planet’s formation pathway. Based on new high-resolution spectroscopy of AF Lep A, we measure a uniform set of stellar parameters and elemental abundances (e.g., [Fe/H] = −0.27 ± 0.31 dex). The planet’s dynamical mass ( ${2.8}_{-0.5}^{+0.6}$ M _Jup ) and orbit are also refined using published radial velocities, relative astrometry, and absolute astrometry. We use petitRADTRANS to perform chemically consistent atmospheric retrievals for AF Lep b. The radiative–convective equilibrium temperature profiles are incorporated as parameterized priors on the planet’s thermal structure, leading to a robust characterization for cloudy self-luminous atmospheres. This novel approach is enabled by constraining the temperature–pressure profiles via the temperature gradient $(dlnT/dlnP)$ , a departure from previous studies that solely modeled the temperature. Through multiple retrievals performed on different portions of the 0.9–4.2 μ m spectrophotometry, along with different priors on the planet’s mass and radius, we infer that AF Lep b likely possesses a metal-enriched atmosphere ([Fe/H] > 1.0 dex). AF Lep b’s potential metal enrichment may be due to planetesimal accretion, giant impacts, and/or core erosion. The first process coincides with the debris disk in the system, which could be dynamically excited by AF Lep b and lead to planetesimal bombardment. Our analysis also determines T _eff ≈ 800 K, $log(g)≈ 3.7$ dex, and the presence of silicate clouds and disequilibrium chemistry in the atmosphere. Straddling the L/T transition, AF Lep b is thus far the coldest exoplanet with suggested evidence of silicate clouds.